Preliminary Report on the Fecundity of Mytilicola orientalis - Johnson, Eugene A.; Chew, Kenneth K. (Journal of the Fisheries Research Board of Canada, 1969)
Egg cases of the endoparasitic copepod Mytilicola orientalis Mori were examined from samples dissected from Pacific oysters (Crassostrea gigas) and bay mussels (Mytilus edulis) from Humboldt Bay, California, Yaquina Bay, Oregon, and Willapa Bay and Hood Canal, Washington. There was little variation between the number of eggs in both egg cases from an individual female. On the bases of two egg sacs per female approximately 252–368 eggs are produced.